Implementasi Hubungan Nilai-Nilai Pancasila di PT. Shung Chang Purbalingga Jawa Tengah - Kangza Ardila; Nadea Indah Franesthi; Akhti Khasanah; Fakhry Ali; Siti Maghfiroh (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Pancasila Industry is a concept that connects operations in the industrial sector with an economy based on Pancasila with justice. In addition to being the foundation of the state, Pancasila is also used as a reference for companies in Indonesia coupled with the Law on Labor... The application of Pancasila values in the industrial sector is very important. Through the values of Pancasila, it is hoped that the company will not be arbitrary to its workers so that it can create a work environment that is harmonious, harmonious, upholds tolerance and achieves welfare for its workers. PT Shung Chang Purbalingga is one of the largest companies in Central Java engaged in the manufacturing industry. PT Shung Chang produces wigs that are later imported to other countries such as Korea, Japan, and China. The purpose of this study is to examine more deeply the application of the Pancasila industry at PT. Shung Chang Purbalingga and how the forms of application of the five Pancasila at PT. Shung Chang. The method used in the research is qualitative with a case study approach. Researchers get research data from interviews, documentation and other supporting sources. The results of the study explain that PT Shung Chang in its operation has been in accordance with the Pancasila economy and reflects the values of Pancasila.